1999
DOI: 10.1128/jcm.37.12.4131-4134.1999
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Streptococcus pyogenes Serotype M1 and M3 Isolates from Patients in Japan from 1981 to 1997

Abstract: Streptococcus pyogenes isolates obtained in 1981 to 1997 from patients and healthy subjects were characterized by pulsed-field gel electrophoresis (PFGE) patterns, biotyping, and the presence of spe genes encoding streptococcal pyrogenic exotoxins. Changes in the profiles were shown in the serotype M1/T1 isolates from pharyngitis over this period, but not in serotype M3/T3 isolates. The characteristics of isolates from patients with toxic shock-like syndrome (TSLS) were comparable to those of the other isolate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2000
2000
2009
2009

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 18 publications
1
6
0
Order By: Relevance
“…When we analyzed the GAS isolates used in this study by PFGE after SmaI digestion, we found that their PFGE patterns agreed with those reported previously (Stanley et al , 1995; Murase et al , 1999) (Fig. 1).…”
Section: Resultssupporting
confidence: 89%
“…When we analyzed the GAS isolates used in this study by PFGE after SmaI digestion, we found that their PFGE patterns agreed with those reported previously (Stanley et al , 1995; Murase et al , 1999) (Fig. 1).…”
Section: Resultssupporting
confidence: 89%
“…We also found identical PFGE patterns in GAS isolates obtained from different diseases, showing that strains displaying different genetic backgrounds have the ability to adhere, colonize and infect distinct human sites. Other authors have reported GAS isolates that display the same PFGE pattern as causes of both invasive and non-invasive disease (Descheemaeker et al , 2000; Murase et al , 1999; Nakashima et al , 1997).…”
Section: Discussionmentioning
confidence: 97%
“…(2000) have suggested the existence of another pathway for the invasion. In addition, the worldwide resurgence in severe invasive diseases is highly linked to serotype M1 and M3 (Kiska et al ., 1997; Murase et al ., 1999), and M1 and M3 proteins have been reported to be more effective in invasion than M6 protein (Berkower et al ., 1999; Dombek et al ., 1999). In other words, serotype M1 and M3 GAS strains may induce apoptosis more efficiently in epithelial cells than other serotypes.…”
Section: Discussionmentioning
confidence: 99%